2020
DOI: 10.1177/0954411920944039
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling of media flow through perfusion-based bioreactors for bone tissue engineering

Abstract: Bioreactor system has been used in bone tissue engineering in order to simulate dynamic nature of bone tissue environments. Perfusion bioreactors have been reported as the most efficient types of shear-loading bioreactor. Also, combination of forces, such as rotation plus perfusion, has been reported to enhance cell growth and osteogenic differentiation. Mathematical modeling using sophisticated infrastructure processes could be helpful and streamline the development of functional grafts by estimating and defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The tool has been applied in some tissue engineering studies, to examine microfluidics in bioreactor systems (Geris et al, 2016). In most cases, in silico modeling was performed using a simplified geometry (e.g., a cylinder), idealized by parameterization to reduce the computational burden (Zhao et al, 2019;Ramani-Mohan et al, 2018;Egger et al, 2017;Nokhbatolfoghahaei et al, 2020;Pereira et al, 2021;Melke et al, 2020). Parameterization with porosity and permeability allows the geometry to be considered as a porous domain to which Darcy flow model may be applied.…”
Section: Discussionmentioning
confidence: 99%
“…The tool has been applied in some tissue engineering studies, to examine microfluidics in bioreactor systems (Geris et al, 2016). In most cases, in silico modeling was performed using a simplified geometry (e.g., a cylinder), idealized by parameterization to reduce the computational burden (Zhao et al, 2019;Ramani-Mohan et al, 2018;Egger et al, 2017;Nokhbatolfoghahaei et al, 2020;Pereira et al, 2021;Melke et al, 2020). Parameterization with porosity and permeability allows the geometry to be considered as a porous domain to which Darcy flow model may be applied.…”
Section: Discussionmentioning
confidence: 99%
“…Rotating bioreactors offer major advantages over spinner flasks since they also control the supply of oxygen and exert low fluid shear stress and turbulence ( Kimelman-Bleich et al, 2011 ; Weszl et al, 2012 ; Song et al, 2013 ; Shekaran et al, 2015 ; Song et al, 2016a ; Demir et al, 2018 ; Westman et al, 2019 ; Daulbayev et al, 2020 ; Nokhbatolfoghahaei et al, 2020a ; Nokhbatolfoghahaei et al, 2020b ; Nokhbatolfoghahaei et al, 2020c ). The most common rotating wall bioreactor is formed by two concentric cylinders: 1) the outer one is a culture chamber and accommodates the cellularized scaffold, submerged in culture medium, while 2) the inner cylinder is static and permits gas exchange ( Figure 1B ).…”
Section: In Vitro Approaches To Mimic Interstitial Fluid Flow: An Overview Of Biomechanical Cluesmentioning
confidence: 99%
“…Among these, 3D in vitro fluidic macroscale (i.e., spinner flasks, rotating wall vessels), milliscale (customized perfusion bioreactors), and microscale systems (i.e., microfluidic devices) appear very promising to overcome the limitations of 2D cultures. These devices allow a fine tuning of dynamic interstitial perfusion ( Wittkowske et al, 2016 ; Yuste et al, 2021 ), a full understanding of cell-cell and cells-ECM interactions and, overall, a better comprehension of in vivo biological mechanisms ( Kim et al, 2007 ; Esch et al, 2015 ; Arrigoni et al, 2017 ; Carvalho et al, 2018 ; Wang et al, 2018 ; Nokhbatolfoghahaei et al, 2020a ). So far, good outcomes have been achieved in reproducing structural, functional, and mechanical properties of tissues using perfused platforms, including lung alveoli and bronchioles ( Huh et al, 2010 ; Ott et al, 2010 ; Price et al, 2010 ; Stucki et al, 2015 ), renal tubules and glomeruli ( Humes et al, 1999 ; Humes et al, 2004 ; Jang and Suh, 2010 ; Wilmer et al, 2016 ), small intestine ( Kimura et al, 2008 ; Imura et al, 2009 ; Pusch et al, 2011 ; Schweinlin et al, 2016 ), liver ( Kane et al, 2006 ; Tsang et al, 2007 ; Yamada et al, 2007 ; Domansky et al, 2010 ; Elbakary and Badhan, 2020 ) and the blood-brain barrier ( Booth and Kim, 2012 ; Griep et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In an incubator, the combined blood vessel bioreactor can provide a relatively closed, non-toxic, sterile environment with adequate oxygen supply and stable temperature for vascular construction. 22,23 first reported the successful construction of tissue-engineered small vessels using a blood vessel bioreactor in 1999. The findings revealed that the vessels' morphology and histology were comparable to that of native blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the researchers designed blood vessel bioreactor, which could simulate the throbbing of blood vessels circulating in the body, and successfully used it to construct TEVG. In an incubator, the combined blood vessel bioreactor can provide a relatively closed, non‐toxic, sterile environment with adequate oxygen supply and stable temperature for vascular construction 22,23 . Niklason et al first reported the successful construction of tissue‐engineered small vessels using a blood vessel bioreactor in 1999.…”
Section: Introductionmentioning
confidence: 99%